1968
DOI: 10.1063/1.1668221
|View full text |Cite
|
Sign up to set email alerts
|

Torsion–Vibration–Rotation Interactions in Methanol. I. Millimeter Wave Spectrum

Abstract: In a study of internal rotation in methanol, the millimeter wave spectra of CH3OH, CD3OH, and CH3OD have been investigated between 90 and 200 Gc/sec. In the analysis of the spectra, torsion–vibration–rotation interactions were treated as adjustable parameters in semiempirical formulas. Kivelson's formula for a-type ΔK = 0 transitions was tested over a wide range of quantum numbers. It reproduced the CH3OH and CD3OH spectra quite well, but the approximations used in the calculations appear to start breaking dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
201
3

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 552 publications
(218 citation statements)
references
References 47 publications
13
201
3
Order By: Relevance
“…Values of r^ = 1.44 Ä are found in the liquid phase from neutron [12] and X-ray [13,14] diffraction. These values are slightly larger than the ones reported for the gas phase, 1.42-1.43 Ä [15][16][17][18]. The value 1.44 Ä is used here.…”
Section: Experiments and Simulationscontrasting
confidence: 42%
“…Values of r^ = 1.44 Ä are found in the liquid phase from neutron [12] and X-ray [13,14] diffraction. These values are slightly larger than the ones reported for the gas phase, 1.42-1.43 Ä [15][16][17][18]. The value 1.44 Ä is used here.…”
Section: Experiments and Simulationscontrasting
confidence: 42%
“…Energy levels are labelled by the total angular momentum J, its projection along the symmetry a-axis k or K = |k|, the torsional vibration quantum number v t and the torsional sublevel quantum number σ. The threefold symmetric torsional barrier in methanol indeed leads to the existence of three torsional symmetry states, usually designated A, E 1 and E 2 corresponding to σ = 0, +1, −1, respectively (Lees & Baker 1968). For the E species, k ≥ 0 states are degenerate with the E 2 k ≤ 0 states, and vice versa.…”
Section: Appendix A: Spectral Designationmentioning
confidence: 99%
“…This model is based on the work of Lin & Swalen (1959), Kirtman (1962), and Lees & Baker (1968). This formalism and our code 1 have been completely described in previous studies and applied with success to a number of internal rotor molecules observed in the interstellar medium, i.e.…”
Section: Theoretical Modelmentioning
confidence: 99%